Psychiatric symptoms in adult patients with cerebral palsy: A cohort study - Pizzighello, Silvia; Uliana, Marianna; Michielotto, Martina; Pellegri, Alda; Vascello, Matteo G. F.; Piccoli, Sara; Martinuzzi, Michela; Martinuzzi, Andrea (Frontiers in Neurology, 2022)
Background: Patients with cerebral palsy (CP) have an increased risk of developing mental health disorders. Aims: This paper aims to investigate the occurrence of psychiatric symptoms in adults with CP and to explore the relation with clinical and psychosocial variables. Method and Procedures: We included 199 adults with a diagnosis of CP. The chi square and the Mann Whitney U tests were used to compare clinical and psychosocial variables, the level of perceived disability and the type of observed parental style in patients with and without psychiatric symptoms. Logistic regression analysis was used to identify variables that could predict the occurrence of mental health disorders. Outcome and Results: Anxiety and psychosis were the most represented disorders. Age, living status, assumption of drugs, motor, manual and global impairment were significantly different between patients with and without psychiatric symptoms. Similarly, a different parental style was observed between the two groups. Logistic regression indicated that living status, prescribed drugs, parental style and the perceived disability in getting along with others predicted the occurrence of psychiatric symptoms. Conclusions and implications: Results suggest that patients with and without psychiatric symptoms have different clinical and psychosocial characteristics. Some variables should be considered as potentially affecting the mental health of patients with CP.